Transformasi Manajemen Publik Berkelanjutan di Kabupaten Purbalingga - Nurhamzah, Fachrizal; Erina Darni, Isna (Journal of Comprehensive Science, 2025)
Sustainable public management transformation is a crucial issue in the era of globalization which is characterized by the complexity of the challenges faced by governments around the world. This study aims to explore best practices, obstacles, and driving factors in the transformation of public management in Purbalingga Regency, Indonesia. With a descriptive-exploratory qualitative approach, data was obtained through in-depth interviews, observations, and analysis of official documents. The need to manage resources responsibly, improve the efficiency of public services, and meet public demands for transparency and accountability is increasingly urgent. Sustainable public management transformation is not only an option, but also a necessity to ensure the welfare of the community in the future. This research aims to identify approaches and strategies that can be applied in supporting the transformation and explore the driving factors and inhibitions in its implementation. This study uses a qualitative approach with a descriptive-exploratory design. The results of the study show that the use of information technology such as e-government plays an important role in improving the efficiency and transparency of public services. Cross-sector collaboration between governments, civil society, and the private sector has proven to be a key strategy in achieving successful transformation. Community involvement in the planning and implementation of public policies increases the relevance of policies to local needs. However, challenges such as resistance to change and limited resources still hinder this transformation process. Therefore, a holistic and sustainability-oriented strategy is needed to overcome these obstacles. The transformation of sustainable public management in Purbalingga Regency is a strategic step in realizing inclusive, adaptive, and responsive governance to global dynamics and local needs.